Gender Stereotyping in Schools: A Study in Rural Assam - Das, ADITI (International Journal of Psychosocial Rehabilitation, 2024)
Developing countries face number of problems such as poverty, unemployment, malnutrition, poor educationalinfrastructure, of which one of the most fundamental problems is the gender disparity in schooling. Schoolenrolments of girls are lower than the boys indicating that girls are disadvantaged in access to education. Apartfrom various factors that affect gender disparity in schooling, an important fundamental constraint that restrictsattainment towards gender equality is gender stereotyping in school especially in class room activity. Thispaper tries to identify whether gender stereotype exist in the classroom activity in the schools under study. 18government schools have been selected from six blocks from three districts of Assam and a sample of 90 inservice teacher has been collected. A semi structured interview was also conducted to understand the attitude ofthe teacher towards gender stereotyping in class room activities.